Study of Variation of the Sciatic Nerve in Cadavers: A Descriptive Cadaveric Analysis - Thakur, Umeshwar Prasad; Yadav, Pranav Kumar; Shah, Tirtha Narayan; Rain, Abdullah; Bhandari , Keshav Raj (International Journal of Silkroad Institute of Research and Training, 2025)
Background: The sciatic nerve, the longest and widest nerve in the human body, is prone to anatomical variations that may influence clinical procedures like sciatic nerve block, hip surgeries, and management of sciatica. This study aimed to investigate the anatomical variations of the sciatic nerve in cadavers to aid clinicians in minimizing iatrogenic complications. Method: A total of 50 adult cadavers (45 male, 5 female) were examined through systematic dissection of the gluteal region. The emergence, course, and division level of the sciatic nerve were observed and classified. Result: Out of 50 cadavers, 38(76%) exhibited the classical pattern, while 12(24%) showed variations. High division of the sciatic nerve (above the piriformis) was seen in 8 cases (16%), including 7 males and 1 female. In 3 cases (6%), the nerve divided within the piriformis, and in 1 cadaver (2%), the common fibular nerve passed above the piriformis while the tibial nerve passed below. Conclusion: The study highlights the prevalence of anatomical variations in the sciatic nerve, which has significant implications in regional anesthesia and surgical procedures. Recognizing such variants is essential for preventing nerve damage and optimizing patient outcomes.